Residue dynamics of Luna experienceÂ® on apple - Dubey, Jatiender Kumar; Patyal, Surender Kumar; Katna, Sapna; Devi, Nisha; Sharma, Ajay; Chauhan, Avinash (Indian Journal of Plant Protection, 2020)
Luna Experience 400 SC (fluopyram + tebuconazole) is a systemic suspension concentrate fungicide, effective against powdery mildew and scab on apples, grapes and pear worldwide. Human safety is an important issue along with the environmental hazards created by the different chemicals being used in crops, hence, in order to study the residue dynamics of these pesticides, trials were carried out at four different locations of Himachal Pradesh and Jammu and Kashmir (J & K) during 2014-15. Fruit and soil samples were collected after spraying these pesticides at X-dose and 2X-dose, extraction was done using QuEChERS method and cleanup by using dispersive solid phase method. Residues of fluopyram along with its metabolite fluopyram benzamide and tebuconazole residues were analysed by gas chromatograph - mass spectrometry. Half-life (RL50) values were found to be 3.9 and 4.7 days for fluopyram and 3.8 and 4.6 days for tebuconazole in apple at X-dose (recommended dose = 125 g a.i./ha ) and 2-X dose (double the recommended = 250 g a.i./ha) dose, respectively. The initial deposits of fluopyram on apple fruits were 0.707 and 1.283 mg/kg and of tebuconazole were 0.826 and 1.334 mg/kg at X and 2-X doses, respectively. Residues dissipated to below detection limit on 20th day and 30th day after spraying, respectively at X and 2-X doses respectively. Residues of fluopyram benzamide were below limit of determination on the day of spray itself.